ALGINATE BASED GASTRO-RETENTIVE RAFT FORMING TABLETS FOR ENHANCED BIOAVAILABILITY OF TINIDAZOLE - Manna, Sreejan; Jayasri, Kanchi; Annapurna, Kancherla Radha; Kanthal, Lakshmi Kanta (International Journal of Applied Pharmaceutics, 2016)
Objective: Tinidazole, a nitroimidazole derivative is having low aqueous solubility which is a major barrier for systemic drug absorption. The aim of the present research was to develop gastro retentive raft forming tablets of tinidazole to achieve prolonged gastric residence time and thus higher bioavailability. Methods: Solid dispersion of tinidazole was prepared by kneading method by using methanol and polyvinylpyrrolidone (PVP). Different concentration of sodium alginate and hydroxypropyl methylcellulose (HPMC) was used to formulate a suitable raft forming tablets and then evaluated for drug content, floating lag time, raft strength, raft volume, raft weight, drug release and release kinetics. Results: Fourier transform infra-red (FT-IR) study confirms compatibility between drug and polymer. The floating lag time was found in the range of 40±4 to 60±5 s for all the formulation. Raft strength for all the formulations was within the range from 3.03±0.12 to 5.92±0.06 g. The raft volume for all the formulation was found within the range of 7.37±1.86 to 9.84±2.76 ml. Raft weight was measured after completion of raft formation for each formulation and was found in the range of 5.21±1.17 to 7.88±1.95 g. In vitro dissolution was carried up to 8 h and percentage of drug release was found to vary between 79.71±2.18 to 94.32±1.79 %. Conclusion: It can be concluded that the combination of solid dispersion and raft formation increases the bioavailability of tinidazole in tablet formulation.